1998
DOI: 10.1111/j.1750-3639.1998.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Up‐Regulates TrkB Protein and Prevents the Death of CA1 Neurons Following Transient Forebrain Ischemia

Abstract: The neurotrophin family of growth factors, which includes Nerve Growth Factor (NGF), Brain‐Derived Neurotrophic Factor (BDNF), Neurotrophin‐3 (NT3) and Neurotrophin‐4/5 (NT4/5) bind and activate specific tyrosine kinase (Trk) receptors to promote cell survival and growth of different cell populations. For these reasons, growing attention has been paid to the use of neurotrophins as therapeutic agents in neurodegeneration, and to the regulation of the expression of their specific receptors by the ligands. BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The present studies approved that it could be persistent, so that exogenous BDNF could resist the proinflammatory cytokines and activate TrkB signal conduction during the treatment of S. pneumoniae meningitis. On the other hand, other studies have shown that BDNF up-regulates TrkB protein and prevents the death of CA1 neurons following transient forebrain ischemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…The present studies approved that it could be persistent, so that exogenous BDNF could resist the proinflammatory cytokines and activate TrkB signal conduction during the treatment of S. pneumoniae meningitis. On the other hand, other studies have shown that BDNF up-regulates TrkB protein and prevents the death of CA1 neurons following transient forebrain ischemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lowenstein and Arsenault (1996) have shown that application of BDNF (and FGF-2-discussed later) onto microdissected dentate granule cells increases their survival and neuronal differentiation by 30-80% (Lowenstein and Arsenault, 1996). Application of BDNF and NGF to cultured hippocampal neurons has also shown to be protective against hypoglycemic damage (Kokaia et al, 1994;Mitchell et al, 1999), ischemia (Ferrer et al, 1998;Mitchell et al, 1999), and ethanol (Mitchell et al, 1999). Further, BDNF knockout mice show an increase in apoptosis specifically in the DG and subventricular zone (Linnarsson et al, 2000)-the two regions that have consistently been shown to exhibit adult neurogenic activity.…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 97%
“…BDNF administration in the cerebrospinal fluid reduced cell death following global ischemia in rats [115], whereas grafting of BDNF-producing fibroblasts diminished ischemic cell death in the hippocampus following transient forebrain ischemia in gerbils [116]. A similar approach with grafted BDNF-transfected fibroblasts protected nerve cells from dying in the area of penumbra in a model of focal cerebral ischemia in rats [117].…”
Section: Trophic Factors and Neuroprotection In Strokementioning
confidence: 99%